Free Amino Acids Analysis in the Venom of the Social Wasp Polistes lanio Under Different Forms of Preservation - Viviana de Oliveira Torres; Raul Cremonezi Piva; William Fernando Antonialli Junior; Claudia Andrea Lima Cardoso (Orbital: The Electronic Journal of Chemistry, 2018)
Venoms of social wasps have in their composition proteins, peptides, among others and several of these compounds were evaluated for their function in the venom, however, there is still no study of the quantification of free amino acids of venom of social wasps. The peptides and proteins of the venom can originate in the medium amino acids or other molecules by the rupture of the peptide bonds. Therefore, the objective was evaluated the composition of the free amino acid in venom of the social wasp Polistes lanio and validated a method for free amino acids analysis using different forms of preservation of this venom. For this, the venom of P. lanio was analyzed direct and partitioned (liquid-liquid with organic solvents) by High Performance Liquid Chromatography. For validation of the amino acids, parameters as linearity, stability and recovery of the assay method were evaluated by the analyzing it fresh or frozen, and before or after extraction with organic solvents. The free amino acids were recovered from these samples at rates ranging from 93.2-99.0%. The data obtained indicate that the freezing, storage and extraction with organic solvents does not lead to an increase in the amino acids content of proteins and peptides.DOI: http://dx.doi.org/10.17807/orbital.v10i1.1005